2016
DOI: 10.30736/jy.v7i1.5
|View full text |Cite
|
Sign up to set email alerts
|

PERBANDINGAN PRODUKTIVITAS AYAM BROILER TERHADAP SISTEM KANDANG TERBUKA (Open House) DAN KANDANG TERTUTUP (Closed House) DI UD SUMBER MAKMUR KECAMATAN SUMBERREJO KABUPATEN BOJONEGORO

Abstract: Penelitian dilaksanakan pada tanggal 20 Mei sampai 25 Juni tahun 2016 dilakukan penelitian di Kandang Terbuka (Open House) dan Kandang Tertutup (Closed House) di UD. Sumber Makmur Kecamatan Sumberrejo Kabupaten Bojonegoro.Tujuan penelitian ini adalah untuk mengetahui perbandingan produktivitas sistem Kandang Open House dan Kandang Closed House ternak ayam broiler di UD. Sumber Makmur Kecamatan Sumberrejo Kabupaten Bojonegoro. Teknik penelitian yang digunakan adalah jenis penelitian pengamatan secara langsung k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…The ration conversion index will increase if the relationship between the amount of internal energy formula and protein content is adjusted technically (Mookiah et al, 2014). moRtality Susanti et al (2016) reported that mortality in one maintenance period of broiler chickens for 5 weeks in closed houses by 4% and opened houses by 5%. Marom et al (2017) stated that high mortality shows the appearance of low production.…”
Section: Feed Conversion Ratiomentioning
confidence: 99%
“…The ration conversion index will increase if the relationship between the amount of internal energy formula and protein content is adjusted technically (Mookiah et al, 2014). moRtality Susanti et al (2016) reported that mortality in one maintenance period of broiler chickens for 5 weeks in closed houses by 4% and opened houses by 5%. Marom et al (2017) stated that high mortality shows the appearance of low production.…”
Section: Feed Conversion Ratiomentioning
confidence: 99%
“…Popularitasnya terus meningkat dan menjadi primadona pada tahun 1980. Dekade terakhir ini pemeliharaan ayam broiler semakin maju dengan adanya teknologi kandang sistem closed house (Susanti, Dahlan, & Wahyuning, 2016). Peternak sudah beralih dalam pemeliharaan yang sebelumnya secara open house ke sistem closed house.…”
Section: Pendahuluanunclassified